The priority of Propositional Justification - Demircioglu, Erhan (Estudios de Filosofía, 2019)
Turri argues against what he calls an “orthodox” view of the relationship between propositional and doxastic justification, according to which (Basis) it is sufficient for S to be doxastically justified in believing p that p is propositionally justified for S in virtue of having reason(s) R and S believes p on the basis of R. According to Turri, (Basis) is false and hence the orthodox view is wrong. Turri offers “an alternative proposal,” the definitive thesis is that the subject’s intellectual abilities explain why a given proposition, p, is justified for her, and argues that, contra the orthodoxy, this proposal leads to explaining propositional justification in terms of doxastic justification rather than vice versa. In this paper, I argue for the following claims: (i) There are good reasons to think that Turri misidentifies “the orthodox view” and his objection thereby misfires, (ii) Even if we assume that Turri’s identification of the orthodox view is correct, his counter-examples to that view are far from being decisive, and (iii) Turri’s own proposal is not “an alternative” to the orthodox view but can be accommodated by it.